Análise da qualidade da água superficial do Rio Subaé, Bahia e influência do uso e ocupação do solo em seu entorno - Santos, Leila Thaíse Santana de Oliveira (2013)
The Subaé river basin (BRS), whose source is located in Feira de Santana-BA and its mouth in the Bay of All Saints, poses serious environmental impacts in its main watercourses arising from dumping of domestic and industrial effluents, agricultural and extractive activities. This study aims to perform analysis of physicochemical processes and microbial surface water has not been studied in the stretch along the main river channel Subaé and analysis of processes for use and occupation of the soil surrounding the BRS. Use map and land use was generated from the RapidEye satellite image, 2010, together with field surveys and through the software ArcGis 9.3, Global Mapper 11 and Envi 4.0, identified five main classes: urban area, bodies water, bare soil, vegetation and agriculture, of which agriculture accounts for 77.6% of the entire basin area, bordering the main river from its source to its mouth. 13 points were defined water collection, geo-referenced throughout the course of the river and Subaé samples were collected in December 2011, April 2012 and November 2012. The results were analyzed based on CONAMA Resolution 357/05 and 430/12 for Class 2 waters sweet, consistent with the proposed framework for the spring and held Pearson correlation to unify the possible relationships of heavy metals and physico- Chemical. The results demonstrate the analyzed parameters, dissolved oxygen (DO), biochemical oxygen demand (BOD), turbidity and phosphate are above the maximum allowable values in most monitoring points, compared with the values of legislation and total coliforms and thermotolerant at all collection points and in all samples had values above that indicated by the legislation. Heavy metals, only Cd and Cr were not detected in any of the monitoring points and none of the collections. The highest concentrations of metals found in descending order were Zn> Mn> Cu> Pb> Ni. The Pearson correlation demonstrated a strong relationship between the physico-chemical parameters and metals. These results are related to the fact that water bodies receiving domestic and industrial effluents from various activities in the area of BRS. By the results it is concluded that the river Subaé presents a high level of degradation in the quality of its waters and represents a health risk for the population living around it. This research will provide subsidy for implementation of actions aimed at the rational use of water resources of BRS, and contribute to scientific studies that allow a better understanding of the real situation of this important and strategic industrial region of Bahia state.